Altered ventral striatal activation during reward and punishment processing in premanifest Huntington's disease: A functional magnetic resonance study - Enzi, Björn; Edel, Marc-Andreas; Lissek, Silke; Peters, Sören; Hoffmann, Rainer; Nicolas, Volkmar; Tegenthoff, Martin; Juckel, Georg; Saft, Carsten (Experimental neurology, 2012)
Recent research using various neuroimaging methods revealed the crucial role of the striatum concerning the neuropathology of Huntington's disease. Degenerative changes located in the basal ganglia are already observable in premanifest stages of Huntington's disease (pre-HD), i.e., before the onset of manifest motor symptoms. Although the impact of the striatum on reward and punishment processing is well-established in healthy subjects, these processes have not been investigated in manifest and premanifest HD subjects using functional magnetic resonance imaging (fMRI) so far. We used the Monetary Incentive Delay Task to investigate valence discrimination in terms of rewarding and punishing cues in 30 pre-HD and 15 healthy subjects. According to the probability of disease onset within the next 5years, pre-HD subjects were categorized as either near to motor symptom onset (pre-HDnear; 9.9 [±2.91] years to onset) or far from manifest disease onset (pre-HDfar; 23.49 [±5.99] years to onset). Compared to pre-HDfar and healthy subjects, pre-HDnear subjects showed a disturbed neuronal differentiation between reward and control anticipation located in the left ventral striatum. In contrast to pre-HDfar and healthy subjects, no significant ventral striatal discrimination between punishing and control cues was detected in pre-HDnear subjects. In the present study, we demonstrated for the first time significant differences in valence discrimination in pre-HDnear subjects compared to pre-HDfar subjects and healthy controls. Altered reward and punishment processing could therefore reflect a motivational deficit that may contribute to the pathogenesis of Huntington's disease. ► Investigation of the ventral striatum as core region of the human reward system. ► Subjects at risk for Huntington's disease (pre-HD) were investigated. ► Functional deficits in reward and punishment processing in pre-HD subjects. ► Voxel-based morphometry was used to control for brain atrophy in pre-HD subjects.